Microenvironmental dynamics in steady-state and stress erythropoiesis - Chong Yang; Toshio Suda (Blood Science)
Anemia is a condition marked by a shortage of red blood cells or hemoglobin, resulting in a diminished ability of the blood to carry oxygen. In response to anemia or hypoxia, the body activates a compensatory mechanism known as stress erythropoiesis. This crucial physiological process results in increased erythrocyte production, particularly in extramedullary sites such as the spleen and liver, to restore adequate oxygen levels. Unlike steady-state erythropoiesis, which primarily occurs in the bone marrow, stress erythropoiesis depends on distinct progenitor cells and signaling pathways within a specialized erythroid niche in adult spleen and liver. This niche provides essential support for the proliferation, differentiation, and maturation of erythroid progenitors during anemic stress. The dynamics within this niche under stress conditions involve complex interactions between progenitor and niche cells. These interactions are regulated by specific molecular signals that adapt to the body’s physiological demands, ensuring an appropriate response to stress. This review explores the cellular and molecular mechanisms governing these processes, highlighting the extrinsic pathways and cellular interactions during stress erythropoiesis. In addition, it underscores the need for future research to translate findings from murine models into therapeutic strategies for treating anemia-related diseases.